1985
DOI: 10.1111/j.1365-2133.1985.tb02321.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin irritation caused by transdermal drug delivery systems during long-term (5 days) application

Abstract: We have studied the skin irritation produced by the prolonged application of transdermal therapeutic systems. The systems were applied to the skin of the back of male volunteers for 120 hours, and sweat accumulation and bacterial growth were studied. In some cases hydrogel discs were attached to the systems. The results showed that sweat accumulation contributed more to the skin irritation than the bacterial overgrowth. The incorporation of hydrogels in the transdermal delivery system may help to reduce skin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…Rawlings et al have reported decreased levels of NMF in the SC of aged skin and attribute the decrease to ultraviolet damage [18]. In contrast, prolonged exposure to sufficiently high levels of water results in various forms of inflammation, irritation, dermatoses, and urticaria [21][22][23][24][25]. Warner et al have reported disruption of the SC following prolonged exposure to water [26].…”
Section: Discussionmentioning
confidence: 99%
“…Rawlings et al have reported decreased levels of NMF in the SC of aged skin and attribute the decrease to ultraviolet damage [18]. In contrast, prolonged exposure to sufficiently high levels of water results in various forms of inflammation, irritation, dermatoses, and urticaria [21][22][23][24][25]. Warner et al have reported disruption of the SC following prolonged exposure to water [26].…”
Section: Discussionmentioning
confidence: 99%
“…Advancements in design and construction of protective garments and wound dressings may reduce the level of skin hydration and dermatitis. Application of optimal hydrocolloid patches that absorb water in both liquid and vapor form can also decrease irritation (63)(64)(65). A natural, pure, and non-woven dressing has been made from calcium alginate fibres (66).…”
Section: Optimal Occlusionmentioning
confidence: 99%
“…These approaches include chemical enhancers, 4,5 iontophoresis, 6,7 electroporation, 8 microneedles, 9,10 sonophoresis 11,12 and laser ablation. 13 Although significant progress has been made in the transdermal delivery of drugs, there still exist many disadvantages such as skin irritation, 14 high production costs 15 and inconvenience. 13 Thus, it is urgent to develop a low-toxic, low-cost, convenient and efficient transdermal delivery system.…”
Section: Introductionmentioning
confidence: 99%